Widely Impaired White Matter Integrity and Altered Structural Brain Networks in Psychogenic Non-Epileptic Seizures - Sone D (Dove Medical Press, 2019)
Daichi Sone,1 Noriko Sato,2 Miho Ota,3 Yukio Kimura,2 Hiroshi Matsuda1 1Integrative Brain Imaging Center, National Center of Neurology and Psychiatry, Tokyo, Japan; 2Department of Radiology, National Center of Neurology and Psychiatry, Tokyo, Japan; 3Department of Neuropsychiatry, Division of Clinical Medicine, Faculty of Medicine, University of Tsukuba, Ibaraki, JapanCorrespondence: Daichi SoneNational Center of Neurology and Psychiatry, 4-1-1 Ogawa-Higashi, Kodaira, Tokyo 187-8551, JapanTel +81-042-341-2711Fax +81-042-344-6745Email daichisone@gmail.comObjective: The underlying neural correlates of psychogenic non-epileptic seizures (PNES) are still unknown and their identification would be helpful for clinicians and patients. This study aimed to reveal details of white matter microstructure and alterations in brain structural networks in patients with PNES by using diffusion tensor imaging (DTI) and graph theoretical connectivity analysis.Methods: Seventeen patients with PNES and 26 age- and sex-matched healthy controls were enrolled. All participants underwent DTI on a 3.0-T MRI scanner, and fractional anisotropy (FA) and mean diffusivity (MD) maps were compared by tract-based spatial statistics. Additionally, the structural networks derived from DTI data were analyzed using graph theory and two different parcellation schemes.Results: Patients with PNES showed widespread decreases in FA and increases in MD, particularly in the deep white matter. In addition, graph theoretical analysis revealed impaired brain networks in PNES, including increased path length, decreased network efficiency, altered nodal topology, and reduced regional connectivity in the right posterior areas.Conclusion: We found widely impaired white matter integrity and impaired brain structural networks in Japanese patients with PNES. These findings contribute to the accumulation of evidence on PNES and may improve understanding of this condition.Keywords: diffusion tensor imaging, brain structural networks, graph theory, psychogenic non-epileptic seizures, magnetic resonance imaging